THE RELATIONSHIP BETWEEN REGULAR ACUPUNCTURE SESSIONS AND DIETARY PATTERN CHANGES IN OBESE PATIENTS - Dwi Binuko, Raafika Studiviani; Agustina, Tri (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
The research addresses the issue of understanding the potential influence of acupuncture sessions on dietary choices in obese patients. While acupuncture's effects on various health aspects have been explored, the direct link between acupuncture frequency and dietary patterns remains relatively underexplored, especially within the context of obesity. The primary objective is to determine whether there exists a significant relationship between the frequency of acupuncture sessions and shifts in dietary consumption patterns. Additionally, the study aims to identify any potential moderating factors, such as individual patient characteristics or demographic variables, that might impact this relationship. A quantitative methodology is employed to measure and analyze the aforementioned relationships. Data is collected from a sample of obese patients who undergo routine acupuncture sessions. The variables of interest include the frequency of acupuncture sessions, changes in dietary factors (such as protein, fat, fiber, and sugar intake), and any alterations in physical activity levels. A multiple regression analysis is utilized to assess the strength and significance of the relationship between acupuncture session frequency and dietary pattern changes while controlling for potential confounding factors. results indicate a statistically significant positive correlation between the frequency of acupuncture sessions and the number of attended sessions, suggesting that patients who engage in more frequent sessions tend to attend more of them. However, the influence of other variables like dietary factors and physical activity on session attendance appears limited. These findings suggest that acupuncture session frequency plays a pivotal role in influencing patient participation, potentially overshadowing the impact of other factors within this context.